Discovery of CRR1-targeted copper deficiency response in Chlamydomonas reinhardtii exposed to silver nanoparticles. Issue 4 (21st April 2019) - Wang, Songshan; Lv, Jitao; Zhang, Shuzhen
Abstract: The molecular mechanisms behind the adaptive responses for interactions between organisms and nanoparticles, such as silver nanoparticles (AgNPs), are of great concern. In this study, the transcriptome of freshwater alga Chlamydomonas reinhardtii was characterized via RNA sequencing (RNA-seq) after exposure to a nontoxic concentration of AgNPs (0.5 mg/L). The cytochrome c6 (CYC6) and ferredoxin-5 (FDX5) genes were identified with the greatest increase in expression level, which were indications of the copper deficiency in the algae. Gene set enrichment analysis also showed significant enrichment of copper deficiency responsive genes in the transcriptome of algae exposed to AgNPs. These results indicated that AgNPs induced a copper deficiency response in algae, and the excessive intracellular copper content suggested this was due to functional copper deficiency. This deficiency response was further validated to be regulated by transcription factor CRR1 (copper response regulator 1) according to the assays on the mutant strain with defect of CRR1. To the best of our knowledge, this is the first corroboration of a CRR1-targeted copper deficiency response in algae following AgNP exposure. Given the function of copper in fundamental metabolic pathways, such as photosynthesis and respiration, we propose a potential role of CRR1-targeted copper deficiency as an adaptation of algae after exposure to AgNPs.